Gambaran Penyakit Covid-19 di Puskesmas Cempaka Arum Kota Bandung Tahun 2021 - Utami Muliawati Suherlan; Ratna Dewi Indi Astuti; Adjat S. Rasjad (Bandung Conference Series: Medical Science, 2023)
Abstract. COVID -19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). SARS CoV-2 is a new variant that comes from the coronavirus group. Transmission of the SARS virus occurs through droplets that spread easily when humans interact or have direct contact within a certain distance. However, as the SARS-CoV-2 virus evolves, mutations occur, giving rise to new virus variants with a higher transmission rate. This study aims to determine the incidence, patient characteristics based on age and gender, the severity of symptoms, and the percentage of COVID-19 sufferers in one house at the Cempaka Arum Health Center in Bandung City in 2021. The research method used is a descriptive cross-sectional research method. The research population in this study were COVID-19 patients in the city of Bandung. Meanwhile, the sample in this study were COVID-19 patients in 2021 who were recorded and came for treatment at the Cempaka Arum Health Center in Bandung City. Variables used in this study include incidence, age, gender, speed of transmission, and severity of COVID-19. The data analysis used was univariate. The results showed that the incidence of COVID-19 had decreased, the age of the patients was mostly in the range of 26-61 years (58.5%), the most were women (52.79%), the severity of the symptoms of the patients were generally mild and asymptomatic, and the transmission speed of the disease had increased. It is suggested that in the research, the health workers at the Cempaka Arum Health Center should provide socialization and education to the community for the prevention and control of the COVID-19 case. Abstrak. COVID-19 merupakan penyakit menular yang diakibatkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). SARS CoV-2 ialah varian baru yang berasal dari kelompok coronavirus. Penularan virus SARS- terjadi melalui droplet yang tersebar secara mudah ketika manusia melakukan interaksi atau kontak langsung dalam jarak tertentu Pada awal penyebarannya, daya penularan virus tersebut rata-rata masih tergolong cukup rendah,. Namun semakin lama wabah ini berkembang, terjadi mutasi pada virus SARS-CoV-2 dan memunculkan varian virus yang baru dengan tingkat penularan yang lebih tinggi.Penelitian ini bertujuan untuk mengetahui insidensi kejadian, karakteristik pasien berdasarkan usia dan jenis kelamin, tingkat keparahan gejala dan persentasi penderita COVID-19 dalam satu rumah di Puskesmas Cempaka Arum Kota Bandung pada tahun 2021. Metode penelitian yang digunakan yaitu metode penelitian deskriptif dengan cross sectional. Populasi Penelitian pada penelitian ini adalah pasien COVID-19 di Kota Bandung. Sedangkan, sampel dalam penelitian ini adalah pasien COVID-19 pada tahun 2021 yang terdata dan datang berobat di Puskesmas Cempaka Arum Kota Bandung. Variabel yang digunakan dalam penelitian ini meliputi insidensi kejadian, usia dan jenis kelamin, kecepatan transmisi dan tingkat keparahan COVID-19. Analisis data yang digunakan adalah univariat. Hasil penelitian menunjukkan bahwa insidensi kejadian COVID-19 mengalami penurunan, usia pasien paling banyak kelompok usia 26-61 tahun (58.5%), paling banyak perempuan (52.79%) tingkat keparahan gejala pasien umumnya tanpa gejala dan gejala ringan, kecepatan transmisi pasien mengalami peningkatan. Disarankan dalam penelitian, pihak petugas kesehatan di Puskesmas Cempaka Arum harus memberikan sosialisasi dan edukasi pada masyarakat untuk pencegahan dan pengendalian kasus COVID-19.